ANALISIS KEMAMPUAN REPRESENTASI MATEMATIS SISWA SAAT PEMBELAJARAN DALAM JARINGAN DI MASA PANDEMI COVID-19 - Ngaenun Nangim; Kana Hidayati (UNIVERSITAS MUHAMMADIYAH METRO, 2021)
The ability of mathematical representation becomes a student bridge to connect abstract ideas with logical thinking in order to understand mathematical problems. This qualitative descriptive study aims to analyze the mathematical representation abilities of class XI.IPA students of SMA Ali Maksum Yogyakarta in the online learning during the Covid-19 pandemic. The instrument used was a mathematical representation ability test and written interview guidelines via google form. The data analysis technique used is interactive analysis with the stages of data reduction, data presentation, and making overall conclusions. Analysis of test result data is used to determine the level of mathematical representation ability of students, while the results of interviews are to strengthen test results and determine student learning constraints. The results of this study indicate that the level of students' mathematical representation skills in verbal forms is included in the high category, while visual and symbolic forms are included in the medium category. Constraints that arise when learning online, such as limited learning time, signal stability, difficulty understanding the material, and lack of freedom to ask questions have an effect on the test results obtained.